ChemInform Abstract: The Dual Role of 1, 8‐Diazabicyclo[5.4.0]undec‐7‐ene (DBU) in the Synthesis of Terminal Aryl‐ and Styryl‐Acetylenes via Umpolung Reactivity. Issue 6 (21st January 2016) - Morri, Ashok Kumar; Thummala, Yadagiri; Doddi, Venkata Ramana
Abstract: The title synthesis proceeds via an elimination/umpolung/protonation sequence and doesn′t apply to the synthesis of alkyl‐acetylenes.